SENIOR ENGLISH TEACHERS’ IMPLEMENTATION OF DIGITAL LEARNING IN ENGLISH CLASSES: PRACTICES AND CHALLENGES - Sa'diyah, Retni Hanifatus; Kusrini, Endang (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This study aimed to examine teachers’ practices and challenges in implementing digital learning in English classrooms, including the types of digital learning platforms they use, the challenges they face, and the strategies they use to address them. This study used a qualitative method. The researcher used semi-structured interviews with open-ended questions and observations to collect the data. This study was conducted at MAN 1 Purbalingga with four English teachers as the participants. This study used thematic analysis to analyze the data from interviews and observation, the steps were: familiarization with the data, generating initial codes, searching for themes, reviewing the themes, defining and naming themes, and producing the report. This study showed that teachers use various digital learning platforms, including Kahoot!, Canva, Google Classroom, and Google Docs. Teachers face several challenges in implementing digital learning, those are technical issues and connectivity problems, limited access to technology, equitable access to technology, and resistance to change. Teachers have implemented several strategies to address these challenges, including collaboration with colleagues and the IT department, attending professional development, alternative offline activities, and troubleshooting. In addition, digital learning offers advantages such as enhanced student engagement, personalized instruction, and interactive learning opportunities. Teachers believe that digital learning has made learning more competitive and enjoyable, allowing students to take control of their learning. The study highlights the importance of ongoing professional development and technical support for teachers to effectively integrate digital learning into their teaching practices.